GAMBARAN FAKTOR YANG MEMPENGARUHI PILIHAN KONSUMEN TERHADAP PEMBELIAN OBAT BEBAS DI APOTEK “X” SURAKARTA - Manek, Yohanes Stephen; Ariastuti, Reni; Sakti Pambudi, Risma (Melekliterasi Press, 2023)
Over the counter drugs are drugs that can be purchased freely at drug stores such as pharmacies, supermarkets, and drug stores. Drug selection can be influenced by several factors such as drug effectiveness, price, packaging design, safety, brand, promotions and recommendations from other parties. People often get drug information through other and print or electronic media advertisements, which are the most impressive types of information and are easy to understand. This research aims to determine factors that influence consumer choices regarding purchasing over-the-counter drugs at drug store